Weak Magnetic Storms Can Modulate Ionosphere‐Plasmasphere Interaction Significantly: Mechanisms and Manifestations at Mid‐Latitudes. Issue 11 (26th November 2019) - Kotov, D.V.; Richards, P.G.; Truhlík, V.; Maruyama, N.; Fedrizzi, M.; Shulha, M.O.; Bogomaz, O.V.; Lichtenberger, J.; Hernández‐Pajares, M.; Chernogor, L.F.; Emelyanov, L.Ya.; Zhivolup, T.G.; et al.
Abstract: A comprehensive study of the response of the ionosphere‐plasmasphere system at mid‐latitudes to weak (Dstmin > −50 nT) magnetic storms is presented. For the first time, it is shown that weak magnetic disturbances can lead to significant modulation of ionosphere‐plasmasphere H + ion fluxes. It is found that this modulation is caused by the enhancements/reductions of the topside O + ion density, which is induced by F2‐layer peak height rise and fall during the storms. The F2‐layer motion is caused by thermospheric wind changes and by a penetration electric field. Both drivers are closely related to the changes in the Bz component of interplanetary magnetic field. The most prominent manifestation of the H + ion flux modulation is strong changes in H + ion fraction in the topside ionosphere. This study also indicates that the NRLMSISE‐00 model provides the correct relative changes of neutral H density during weak magnetic storms and also that there is a compelling need to include geomagnetic activity indices, in addition to solar activity (F10.7 ), as input parameters to empirical topside ionosphere models. Key Points: Weak magnetic storms cause notable modulation of the ionosphere‐plasmasphere H + ion fluxes and prominent effects in the topside ionosphere The modulation is caused by the topside O + ion density changes induced by F2‐layer peak up/down lifting F2‐layer peak vertical motion is related to the changes in the Bz component of interplanetary magnetic field